2020
DOI: 10.32322/jhsm.665105
|View full text |Cite
|
Sign up to set email alerts
|

Yoğun bakım ünitesinde takip edilen ergen ilaç intoksikasyonların retrospektif değerlendirilmesi

Abstract: Yoğun bakım ünitesinde takip edilen ergen ilaç intoksikasyonlarının retrospektif değerlendirilmesi Retrospective evaluation of adolescent drug intoxications followed in the intensive care unit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…By suicide attempt they express themselves to seek help or take attention rather than desire to die (18,47). It was shown that, the most common method in suicide attempts in adolescence is drug intake (52,53). However, in completed suicides, the most common methods have been reported as suffocation, firearm, poisoning and high jump (8).…”
Section: Methods Of Suicidementioning
confidence: 99%
“…By suicide attempt they express themselves to seek help or take attention rather than desire to die (18,47). It was shown that, the most common method in suicide attempts in adolescence is drug intake (52,53). However, in completed suicides, the most common methods have been reported as suffocation, firearm, poisoning and high jump (8).…”
Section: Methods Of Suicidementioning
confidence: 99%
“…İntoksikasyon; hayatı tehdit etme potansiyeli olan toksik veya toksik olmayan (yüksek doz) maddelerin yanlışlıkla veya intihar amaçlı alınması sonucu vücudun normal fonksiyonlarının bozulması olarak tanımlanmaktadır [1][2][3] . Literatürde intoksikasyona bağlı mortalite oranı %0-5,5 aralığında bildirilmiştir 4,5 .…”
Section: Introductionunclassified
“…İlaç intoksikasyonlarının en önemli nedenini %75,7 ile intihar amaçlı alımlar oluşturmaktaydı. Literatürde de ilaç intoksikasyonlarının en sık sebebinin intihar amaçlı olduğu belirtilmektedir 1,3,19 . "Bireyin istemli olarak yaşamına son vermesi" olarak tanımlanan intihar davranışı sağlık açısından önem taşıyan ve bununla birlikte ekonomik, kültürel, toplumsal ve hukuki yönleri olan bir sorundur 10,20,21 .…”
Section: Introductionunclassified
See 1 more Smart Citation